AN INVESTIGATION OF THE PHASE BEHAVIOR OF AN AQUEOUS SYSTEM THAT CONTAINS A POLYAMPHOLYTE AND POLY(ETHYLENE GLYCOL) - Waziri, S. M. (2020)
The phase behavior of aqueous two-phase polymer system containing poly(ethylene glycol) and a synthetic polyampholyte in 0.1 N KCl was studied as a function of pH. The top phase was poly(ethylene glycol)-rich and the bottom phase was polyampholyte-rich. The binodal curve was found to move towards lower concentrations of polymers with increasing pH as a result of decreased solubility of the polyampholyte. Phase compositions were correlated using a model based on Flory- Huggins theory. Also, a model based on excluded volume theory was used to correlate the binodal curve.